Effect of molybdate and sulfate alone and in combination overload intake on copper outcome in mature male rat: Muhammad M. Al-Ani and Duraid A. Abbas - Abbas, Duraid A. (The Iraqi Journal of Veterinary Medicine, 2017)
This study was designed to investigate the effect of molybdate and sulfate overload alone or in combination overload intake on copper outcome in mature male rats. Twenty eight adult male rats were housed and randomly divided into four equal groups and treated as follows for 60 days: control, groups (T1) rats received sodium molybdate 50 mg/kg B.W and (T2) rats of this group were given orally 500 mg/kg B.W of sodium sulfate. Animals in the (T3) group were given sodium molybdate and sodium sulfate in combination at half dose in comparison with T1 and T2 doses. The severity of toxic symptoms were more noticed at the end of experiment especially in T1 followed by T2, while T3 showed the least toxic symptoms, also the body weight change recorded weight loss during the experiment period at the same following order T1, T2 followed by T3 in comparison with control group that showed normal increase in weight. Biochemical results showed a significant decline in serum glutathione and an increase in serum creatinine, bilirubin and blood urea nitrogen at the same pattern in all treated groups positively proportional with the course of experiment. This was attributed to the recorded deficiency in serum copper that in consequence possibly induced anemia and oxidative changes in T1 and T2 groups, but the addition of sulfate to molybdate at half doses recorded less severity of copper deficiency signs and less toxic consequences indicating a sort of antagonistic effect